Protective effects of mefunidone on ischemia-reperfusion injury/Folic acid-induced acute kidney injury - Li, Jiajia; Jiang, Yupeng; Dai, Qin; Yu, Yue; Lv, Xin; Zhang, Yan; Liao, Xiaohua; Ao, Liyun; Hu, Gaoyun; Meng, Jie; Peng, Zhangzhe; Tao, Lijian; et al. (Frontiers in Pharmacology, 2022)
Renal ischemia-reperfusion injury (IRI) is one of the most common causes of acute kidney injury (AKI). It poses a significant threat to public health, and effective therapeutic drugs are lacking. Mefunidone (MFD) is a new pyridinone drug that exerts a significant protective effect on diabetic nephropathy and the unilateral ureteral obstruction (UUO) model in our previous study. However, the effects of mefunidone on IRI-induced AKI remain unknown. In this study, we investigated the protective effect of mefunidone against IRI-induced AKI and explored the underlying mechanism. These results revealed that mefunidone exerted a protective effect against IRI-induced AKI. In an IRI-induced AKI model, treatment with mefunidone significantly protected the kidney by relieving kidney tubular injury, suppressing oxidative stress, and inhibiting kidney tubular epithelial cell apoptosis. Furthermore, we found that mefunidone reduced mitochondrial damage, regulated mitochondrial-related Bax/bcl2/cleaved-caspase3 apoptotic protein expression, and protected mitochondrial electron transport chain complexes III and V levels both in vivo and in vitro, along with a protective effect on mitochondrial membrane potential in vitro. Given that folic acid (FA)-induced AKI is a classic model, we used this model to further validate the efficacy of mefunidone in AKI and obtained the same conclusion. Based on the above results, we conclude that mefunidone has potential protective and therapeutic effects in both IRI- and FA-induced AKI.